IMPORTANT LESSONS FROM AFRICAN HUMAN RIGHTS MECHANISM FOR ASEAN: COMMON PATH AND SELF-ENFORCING EQUILIBRIA - Rachminawati; Khairil Azmin Mohktar (International Law Department, Faculty of Law Universitas Padjadjaran, 2020)
AbstractIdeally, regional regimes are promising for investigating and remedying human rights violations. This manuscript focuses on the establishment process of regional mechanisms in Africa, specifically on the similarities and dissimilarities among them and look at how the enforcement mechanisms work. It seeks and analyses the process of creating a mechanism to protect individuals' rights in the African region, and present thoughts about how the institution can improve in protecting their peoples' human rights. According to the African experience, institutional building is a long process requiring flexibility and adaptiveness to many conditions facing ahead. As it goes with many uncertainties, all stakeholders, especially those in power, have strong and proactive leadership. In this regard, ASEAN can follow African states’ path to seek and build their human rights mechanisms under their interest as well as other regions’ common paths, such as establishing a commission followed by a court. Further, Africa succeeded in creating a Self-Enforcing Equilibria where African states and elites believe that they can violate the rule and would be worse off if they did so. It has passed this step successfully by establishing human rights institution, including human rights court, to avoid that. Conclusively, African proves that human rights can be protected and promoted without damaging state sovereignty and along the principle of non-interference. Therefore, ASEAN can learn from African's experience. To begin with, ASEAN is unnecessary to have the ideal human rights convention; at the beginning, it shall focus on what it needs and what can be agreed upon. Keywords: ASEAN, Regional Human Rights, Self-Enforcing Equilibria AbstrakSecara ideal, rezim hukum regional menjanjikan dalam menyelidiki dan menyelesaikan pelanggaran hak asasi manusia. Tulisan ini memfokuskan diri pada proses pembentukan mekanisme regional di Afrika, terutama berkenaan persamaan dan perbedaan yang ada, serta meneliti cara kerja penegakan hukum yang ada. Tulisan ini turut menganalisis proses pembentukan mekanisme dalam melindungi hak individu di Afrika, dan memberikan pandangan bagaimana institusi terkait dapat mengembangkan diri dalam melindungi hak asasi manusia. Berdasarkan pengalaman Afrika, pembentukan institusi adalah proses panjang yang membutuhkan fleksibilitas dan adaptasi terhadap situasi masa depan. Oleh karena ketidakpastian yang ada, seluruh pihak yang terkait, terutama yang berkuasa, memiliki kepemimpinan yang kuat dan proaktif. ASEAN dapat mencontoh langkah negara Afrika dalam membangun mekanisme hak asasi manusia seturut kepentingannya dan juga mencontoh langkah umum wilayah lain, seperti membentuk komisi dan pengadilan. Afrika berhasil membentuk self-enforcing equilibria, di mana negara dan pemimpin Afrika sadar bahwa aturan tersebut dapat dilanggar, namun dengan konsekuensi yang buruk. Afrika telah membentuk institusi hak asasi manusia, termasuk pengadilan hak asasi manusia, untuk mencegah hal tersebut. Pada akhirnya, Afrika membuktikan bahwa hak asasi manusia dapat dilindungi dan dimajukan tanpa merusak kedaulatan negara dan sejalan dengan prinsip non-intervensi. Dalam hal ini, ASEAN tidak perlu memiliki konvensi hak asasi manusia pada tahap awal, melainkan memfokuskan diri terhadap kebutuhannya dan apa yang dapat diselesaikan bersama. Kata Kunci: ASEAN, HAM Regional, Self-Enforcing Equilibria